THE EFFECTIVENESS OF X LAB BOOK BASED ON SCIENCE TECHNOLOGY ENGINEERING MATHEMATICS IN REDUCING DOOMSCROLING EITH GAMIFICATION - Zelianti, Dara Resva; Sunti, Sunti; Putri Alim, Annayla Rizki; Sijabat, Elsa Octavia; Pratiwi, Aprilia Naja; Nasution, Riska Amalya (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2025)
The phenomenon of doomscrolling, which is increasingly prevalent among adolescents, has become a new challenge in the digital era. The habit of constantly scrolling and consuming negative information excessively without considering time can seriously impact mental health, reduce concentration ability, and affect academic performance. This condition requires effective and sustainable educational interventions. This community service program aims to reduce doomscrolling behavior among adolescents. The program partners are students aged 12–15 years at SMP Negeri 7 Jambi City. This program employed a Quasi-Experimental method (One Group Pre-test Post-test Design) to evaluate the effectiveness of the intervention. The intervention was carried out through counseling and socialization, along with the implementation of the X-Lab Book based on STEM Builders and Gamification Therapy, supported by group-based science experiment demonstrations as a positive alternative to excessive gadget use. Evaluation was conducted by comparing pre-test and post-test results. The findings demonstrated a decrease in doomscrolling behavior, shown by a reduction in cumulative scores from 935 to 812 after the intervention, indicating improved self-control and healthier digital behavior among participants.